Study on Thermal History Simulation Method of Sedimentary Basin - Han, Feifei (Scientific Journal of Technology, 2026)
The study of thermal history of sedimentary basins is an important part of basin dynamics and hydrocarbon accumulation analysis, which is of great significance for revealing the maturation and evolution of source rocks, hydrocarbon generation and expulsion processes and hydrocarbon accumulation rules. In this paper, two basic methods of basin thermal history restoration are systematically sorted out: tectonic thermal evolution method and paleotemperature scale method. The tectonic thermal evolution method is based on the dynamic model of the lithosphere scale. By simulating the tectonic subsidence and thermal effects of different types of basins such as extension, foreland, craton and strike-slip pull-apart, the basin heat flow history is obtained by forward modeling. The paleo-thermometer method uses the paleo-geothermal information recorded by the paleo-thermometer such as vitrinite reflectance, asphalt reflectance, fission track and (U-Th)/He in the sedimentary strata of the basin to invert the thermal history of the basin. The combination of the two methods can give full play to the advantages of forward modeling and inversion, and make up for the shortcomings of a single method. In addition, this paper also discusses the temperature application range of different paleotemperature scales, the progress of dynamic models and their application examples in the analysis of oil and gas basins. The research shows that the tectonic thermal evolution method is suitable for revealing the origin of the basin and the evolution process of the lithosphere, while the paleo-thermometer method, especially the low-temperature thermochronology method, can accurately describe the thermal history path of the basin. The combined use of the two methods is the development trend of the current basin thermal history research.